Analisis Pengaruh Adopsi Media Sosial Bagi Kinerja UMKM Kota Surabaya TOE Framework - Farizd, Mohammad; Sabila, Radhiya; Martapura, Intania Rachman; Wulansari, Anita (Jurnal Sains dan Teknologi (JSIT), 2023)
The purpose of this study is to analyse the impact of social media adoption on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Surabaya City. The approach used in this research is the Technology-Organisation-Environment (TOE) Framework which considers technological, organisational, and environmental factors that play a role in the adoption of social media by MSMEs. The method used in this research is a survey using a questionnaire as a tool to collect data. Respondents of this research are MSMEs in Surabaya City that have used social media in their business activities. The collected data were analysed through the use of regression analysis techniques to test the research hypothesis. The findings of this study indicate that social media adoption has a positive influence on the performance of MSMEs in Surabaya City. Technological factors have a positive influence on the adoption of social media by MSMEs. In addition, organisational factors also have a positive effect on social media adoption. On the environmental side, it also affects the adoption of social media by MSMEs in Surabaya City. This research shows that the implementation of social media can be an effective strategy for MSMEs in Surabaya City to improve their business performance. MSMEs need to pay attention to technological, organisational, and environmental factors in strengthening their social media adoption. In addition, the government and relevant stakeholders need to provide the necessary support and resources for MSMEs in adopting social media.